2017
DOI: 10.4187/respcare.05545
|View full text |Cite
|
Sign up to set email alerts
|

2016 Year in Review: Mechanical Ventilation

Abstract: The fundamental goals of mechanical ventilation are to improve pulmonary gas exchange and relieve respiratory distress, thus permitting lung and airway healing, while at the same time lessening the risk for iatrogenic complications. This review will summarize some of the advances in mechanical ventilation in 2016, with a particular focus on ventilator-associated clinical challenges and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…Optimal patient-ventilator interaction can help avoid excessive sedation, anxiety, dis-comfort, episodes of fighting with the ventilator, diaphragmatic dysfunction and atrophy due to disuse, potential cognitive alterations, prolonged mechanical ventilation, and additional lung or respiratory muscle injury. 1,2 Research has shown that patients ventilated for Ͼ 24 h who are able to trigger the ventilator have a high incidence of asynchrony during assisted mechanical ventilation. 3 Asynchronies are common throughout mechanical ventilation, occur in all mechanical ventilation modes, and might be associated with outcome, 4 especially when they occur in clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal patient-ventilator interaction can help avoid excessive sedation, anxiety, dis-comfort, episodes of fighting with the ventilator, diaphragmatic dysfunction and atrophy due to disuse, potential cognitive alterations, prolonged mechanical ventilation, and additional lung or respiratory muscle injury. 1,2 Research has shown that patients ventilated for Ͼ 24 h who are able to trigger the ventilator have a high incidence of asynchrony during assisted mechanical ventilation. 3 Asynchronies are common throughout mechanical ventilation, occur in all mechanical ventilation modes, and might be associated with outcome, 4 especially when they occur in clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ventilation (MV) is a life support technique that is routinely used in the intensive care units (ICUs) for patients with life-threatening conditions [1]. Prolonged MV and failure of weaning from MV are two major risk factors for morbidity and mortality in ICU patients and incur high economic costs [2].…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, la lesión pulmonar asociada a la ventilación (VALI), la cual alude a la exacerbación de una lesión pulmonar preexistente debido a factores relacionados con la VM, mientas que VILI hace referencia a los pulmones previamente sanos. [5][6][7] Alrededor de 230 millones de cirugías mayores se realizan cada año en el mundo y la VM es esencial para la anestesia general. Se estima que aproximadamente 20% de los pacientes que recibe VM en estos procedimientos desarrollará VILI.…”
Section: Wwwmedigraphicorgmxunclassified